Factors affecting the learning achievement of undergraduate students through electronic-based instructional delivery of selected industrial marketing topics - Loresco, Pocholo James M. (Animo Repository, 2005)
E-learning has become an important part of education agenda around the world. Though it may be known by different names such as web-based education, distant education, cyber education, networked learning, it typically uses the internet to create an educational experience for students. This study primarily determines the effectiveness of on-line learning delivery of selected topics in the subject Industrial Marketing (INDUMAR). This study compared "on ground" vs. e-based learning to determine if there were any difference in learning achievement of students. Several factors that influence student learning via e-learning have been also studied including their gender and learning styles, and the time spent learning on-line and "off-line". De La Salle students enrolled in INDUMAR are the research subjects. The methods of data collection included questionnaires, and student marks.